Toll-Like Receptors in Ischaemia and Its Potential Role in the Pathophysiology of Muscle Damage in Critical Limb Ischaemia - Hemanshu Patel; Sidney G. Shaw; Xu Shi-Wen; David Abraham; Daryll M. Baker; Janice C. S. Tsui (Cardiology Research and Practice)
Toll-like receptors (TLRs) are key receptors of the innate immune system which are expressed on immune and nonimmune cells. They are activated by both pathogen-associated molecular patterns and endogenous ligands. Activation of TLRs culminates in the release of proinflammatory cytokines, chemokines, and apoptosis. Ischaemia and ischaemia/reperfusion (I/R) injury are associated with significant inflammation and tissue damage. There is emerging evidence to suggest that TLRs are involved in mediating ischaemia-induced damage in several organs. Critical limb ischaemia (CLI) is the most severe form of peripheral arterial disease (PAD) and is associated with skeletal muscle damage and tissue loss; however its pathophysiology is poorly understood. This paper will underline the evidence implicating TLRs in the pathophysiology of cerebral, renal, hepatic, myocardial, and skeletal muscle ischaemia and I/R injury and discuss preliminary data that alludes to the potential role of TLRs in the pathophysiology of skeletal muscle damage in CLI.